OPTIMALISASI PEMBELAJARAN IQRA’ PADA TPQ UBAY BIN KA‘AB MELALUI PENDEKATAN BERBASIS KOMUNITAS - Fanny Hasbi Assyidiqi; Mohammad Imam Safe'i; Muhammad Yufri Bramantio Aly; Zaki Ulien Nuha; Maryono (DEVELOPMENT: Journal of Community Engagement, 2026)
This community engagement program aims to optimize Iqra’ learning at TPQ Ubay bin Ka’ab through a community-based approach (Asset-Based Community Development/ABCD) in Padukuhan Jasem, Pacarejo, Gunungkidul. The program was initiated in response to the mismatch between students’ actual reading abilities and their assigned Iqra’ levels, which affected the effectiveness of Qur’anic learning. This study employed a descriptive qualitative approach within a community service framework. Data were collected through observation, interviews, documentation, and placement tests involving 30 students and two teachers. The intervention included conducting placement tests, regrouping students according to their real abilities, standardizing a 60-minute learning structure, adding learning sessions, and providing teacher mentoring in tajwid and makharijul huruf. The results indicate significant improvement in students’ reading fluency, accuracy in pronunciation, and understanding of long and short vowel rules. In addition, teachers demonstrated greater consistency in correcting recitation based on proper tajwid principles. The ABCD approach effectively strengthened community participation and institutional awareness, leading to a more structured and sustainable Qur’anic learning system.